Hubungan Pola Asuh Orang Tua Dengan Perkembangan Bicara Dan Bahasa Pada Anak Usia Pra Sekolah di PAUD Terpadu Mutiara Bunda Kabupaten Kampar - Syukrianti Syahda; Dhini Anggraini Dhilon; Fitri Apriyanti (Universitas Pahlawan Tuanku Tambusai, 2026)
The growth and development of children in Indonesia still requires serious attention, where the incidence of growth and development delays is still quite high, which is around 5-10% of children experiencing delays in their development in general. Parents play a dominant role in the process of developing communication in children. Language development in each child will be different from one another, such as in terms of mastery, speed and quality.The purpose of this research is to knowing the relationship between parenting patterns and speech and language development in Mutiara Bunda PAUD Terpadu, Kampar Regency. This research is an analytic study with a cross sectional approach. The population in this study is all mothers who have pre-school children aged 3-6 years from January to July 2022 as many as 95 people with the number of samples is the total population of 95 people. The research results obtained are there is the relationship between parenting patterns with speech and language development in pre-school age children with p = 0.000 (p≤0.05). Expected In particular, mothers should educate their children according to their growth and development so that they are able to apply optimal parenting patterns to their children.